DABCO-Intercalated α-Zirconium Phosphate as a Latent Thermal Catalyst in the Reaction of Urethane Synthesis - Osamu Shimomura; Yushi Arisaka; Astrid Rahmawati; Shekh Md. Mamun Kabir; Motohiro Shizuma; Atsushi Ohtaka (Molecules)
The mixture of hexamethylene diisocyanate (HDI) and butanol (BuOH) with the intercalation compound of 1,4-diazabicyclo[2.2.2]octane (DABCO) with α-zirconium phosphate (α-ZrP) has been evaluated as a latent thermal catalyst at varying temperatures. α-ZrP·DABCO did not show activity at 25 °C, but showed a high level of activity at a higher temperature of 80 °C. To clarify the reaction behavior of HDI-BuOH with α-ZrP·DABCO, a viscosity value of 1200 mPa·s·g/cm2 was reached at 80 °C for 30 min. To investigate the deintercalation behavior of DABCO from the α-ZrP interlayer, it was investigated in BuOH and in HDI, respectively, under heated conditions. Interestingly, XRD patterns showed a reduction in α-ZrP·DABCO for the interlayer distance due to the deintercalation of DABCO in BuOH, while no changes associated with the deintercalation of DABCO were observed in HDI. Butanol was found to be important for the deintercalation of DABCO. To examine the reactivity of bifunctional monomers, the reaction of 1,4-butanediol (1,4-BDO) and HDI with α-ZrP·DABCO were investigated to show good reactivity at 80 °C and stability at 40 °C.